Human Resource Accounting Practices and CorporatePerformance of The Listed Manufacturing ‎Companies in Nigeria - Eyo , Ekpo Otu; Adenikinju, Olayinka Omolara.; Oyerogba, Ezekiel Oluwagbemiga.; Oladapo, John; Omojola, Sunday Olusola (International Journal of Accounting and Economics Studies, 2025)
This study examines the effect of Human Resource Accounting (HRA) practices on the corporate ‎performance of listed manufacturing companies in Nigeria between 2013 and 2022. Corporate ‎performance was assessed using Return on Equity (ROE), Return on Capital Employed (ROCE), ‎Return on Assets (ROA), and Earnings Per Share (EPS) as dependent variables. The independent ‎variables include the Historical Cost, Replacement Cost, Opportunity Cost, and Economic Value ‎Approaches to HRA. Firm Size, Firm Age, Ownership Structure, and Audit Quality were ‎included as control variables. Using a mixed-method approach combining survey research and ex-‎post facto design, the study employed both primary and secondary data. Regression results show ‎that HRA practices significantly influence corporate performance, with the Historical Cost ‎Approach demonstrating the strongest positive effect. However, performance trends over the ten years were inconsistent, indicating a lack of strategic alignment between human capital ‎investment and performance outcomes. Guided by Human Capital Theory, Stakeholder Theory ‎, and the Resource-Based View (RBV), the study highlights the critical role of human capital as a ‎strategic and reportable resource. Beyond manufacturing, the findings apply to sectors ‎such as banking, telecommunications, healthcare, and education. The study also compares ‎international best practices, notably IFRS-aligned disclosures in India, South Africa, and the ‎European Union. It recommends the adoption of IFRS-compliant frameworks, especially IAS 19, ‎IAS 38, IFRS 13, and ISSB S1/S2—alongside a national capacity-building program/training for ‎accounting and Human Resource Practitioners. This will strengthen human capital reporting, ‎improve governance, and enhance investor confidence in Nigeria’s manufacturing and broader ‎economic sectors‎.
Keywords: Human Resource; Human Resource Accounting; Corporate Performance; Manufacturing ‎Companies